PERUBAHAN SIKAP SISWA SMAN 1 PARONGPONG TERHADAP HIV/AIDS SETELAH DILAKUKAN PENDIDIKAN KESEHATAN - Pilemon Tarigan; Imanuel Sri Mei Wulandari (Malahayati Nursing Journal, 2020)
ABSTRAC: CHANGES IN ATTITUDE OF SMA N 1 PARONGPONG  STUDENTS TO HIV / AIDS AFTER THE HEALTH EDUCATION  Background: The increase in cases of HIV / AIDS is one thing that is troubling, sufferers are very susceptible to secondary infections caused by a decrease in their immune system. 1/5 of sufferers of HIV / AIDS are teenagers, where this group is vulnerable to exposure to HIV / AIDS through promiscuity. Many efforts have been made to reduce the incidence of new infections, especially in the youth group by providing health education.Purpose: This study was to determine the attitudes of high school students towards HIV / AIDS.Method: The method used is descriptive analytic one group pre-post design using a cross sectional approach. The population in this study were SMA 1 Parongpong students and the sample in this study was 86 students selected using a simple random system.Result: The results obtained before being given health education student attitudes were dominated by negative attitudes as much as 54.7% and after being given health education were dominated by positive attitudes with 88.4%. Wilcoxon test results showed a significant relationship between the provision of health education with changes in attitudes towards high school students towards HIV / AIDS, with a p value 0.05.Conclusion: Adolescents who have positive attitudes are also expected to have positive behavior towards HIV / AIDS, so that they will avoid exposure or transmission of HIV / AIDS. Advice that can be given to maintain this positive attitude is to update accurate information. Key Word: Health Education, Attitude, HIV/AIDS  INTISARI: PERUBAHAN SIKAP SISWA SMAN 1 PARONGPONG TERHADAP HIV/AIDS SETELAH DILAKUKAN PENDIDIKAN KESEHATAN Latar Belakang:Meningkatnya kasus HIV/AIDS merupakan satu hal yang meresahkan, penderita sangat rentan terkena infeksi sekunder yang diakibatkan karena menurunnya sistem imun tubuhnya. 1/5 dari penderita HIV/AIDS adalah kelompok remaja, dimana kelompok ini rentan terekspos dengan HIV/AIDS melalui pergaulan bebas. Banyak upaya yang telah dilakukan guna menurunkan angka kejadian infeksi baru terlebih pada kelompok remaja dengan memberikan pedidikan kesehatan.Tujuan:  Tujuan penelitian ini adalah untuk mengetahui sikap siswa SMA terhadap HIV/AIDS.Metode: Penelitian jenis deskriptif analitik one group pre – post design dengan menggunakan pendekatan cross sectional. Populasi dalam penelitian ini adalah siswa SMA N 1 Parongpong dan sampel pada penelitian ini adalah 86 siswa yang dipilih dengan menggunakan sistem acak sederhana.Hasil Penelitian:  Hasil yang didapatkan sebelum diberikan pendidikan kesehatan sikap siswa didominasi dengan sikap negatif sebnayak 54,7 % dan setelah diberikan pendidikan kesehatan didominasi dengan sikap postif dengan 88,4%. Hasil uji wilcoxon menunjukan adanya hubungan yang bermakna antara pemberian pendidikan kesehatan dengan perubahan sikap pada siswa SMA terhadap HIV/AIDS, dengan p value 0,05.Kesimpulan: Remaja yang mempunyai sikap positif diharapkan juga mempunyai perilaku yang positif terhadap HIV/AIDS, sehingga akan terhindar dari paparan atau penularan HIV/AIDS. Saran yang dapat diberikan untuk mempertahankan sikap positif ini adalah dengan mengupdate informasi yang akurat. Kata Kunci: pendidikan kesehatan, sikap, HIV/AIDS